Improving the Students' Speaking Competence through Jigsaw-Type Cooperative Learning Method by Using Multimedia Devices in Sjakhyakirti Senior High School Palembang - Yuspar Uzer; Yus Vernandes Uzer; Noviati (HOLISTICS, 2021)
The title of the study is improving the students' speaking competence through jigsaw-type cooperative learning methods by using multimedia devices in Sjakhyakirti Senior High School Palembang. The problem of the study, “Is it effective improve the students' speaking competence through Jigsaw-type cooperative learning method by using multimedia devices in Sjakhyakirti Senior High School Palembang?”. The result shows that: The students speaking competence improved. The students weren’t doubts, afraid, shy and lack of confidence in their presentation. They could interact to the presented topic which was discussed in the expert group or jigsaw group with the teacher’s instruction or guidance. The have become more active and have been excited to join it. Besides, when the researcher as the teacher evaluate them to do test orally, the result was good enough. The mean of the score from pre-test and from the cycle one to the following, cycle two always has better progress. The students‟ motivation in the learning improved. The students‟ attitude inside the class during the English teaching and learning process was more cooperative. They become more intensive in following and paying attention to the lesson. Besides, they are more active, excited, and creative in joining the learning. Its means that it is effective in improving the students' speaking competence through jigsaw-type cooperative learning methods by using multimedia devices in Sjakhyakirti Senior High School Palembang. Keywords: Speaking, jigsaw, multimedia devices